Integrated System of Science Learning Based on Social Scientific Issue - Dyah Setyaningrum Winarni; Dyah Rini Indriyanti; Sigit Saptono; Arif Widiyatmoko (International Conference on Science, Education, and Technology, 2022)
Abstrak. Learning based on social issues can certainly answer scientific issues that arise in society. Science learning based on social science issues (SSI) can support learning in implementing theories with conditions or problems that exist in the environment. However, there is no SSI-based science learning system starting from the complete input, process, and output. This literature study aims to provide an overview of an integrated system of SSI-based science learning. The analysis of the articles carried out was taken from electronic databases, namely ERIC, Scopus, and Google Scholar, then directed to national and international journals from 2013-2020. The results of the analysis that the SSI-based integrated system of science learning includes input, process, and output that must be properly integrated for learning purposes.